Use of androgen deprivation and salvage radiation therapy for patients with prostate cancer and biochemical recurrence after prostatectomy - Ghadjar, Pirus; Wenz, Frederik (Strahlentherapie und Onkologie, 2018)
Aim: Overview on the use of androgen deprivation therapy (ADT) added to salvage radiation therapy (SRT) for prostate cancer patients with biochemical recurrence after prostatectomy.MethodsThe German Society of Radiation Oncology (DEGRO) expert panel summarized available evidence published between January 2009 and May 2017, and assessed the validity of the information on outcome parameters including overall survival (OS) and treatment-related toxicity. Results: Two randomized controlled trials and nine relevant retrospective analyses were identified. The RTOG 9601 trial showed an OS improvement for the combination of 2 years of bicalutamide and SRT compared to SRT alone after a median follow-up of 13 years. This improvement appeared to be restricted to those patients with a prostate specific antigen (PSA) level before SRT of ≥0.7 ng/mL. The GETUG AFU-16 trial showed that after a median follow-up of 5 years, the addition of 6 months of goserelin to SRT improved progression-free survival (PFS; based on biochemical recurrence) as compared to SRT alone. ADT in both trials was not associated with increased major late toxicities. Results of retrospective series were inconsistent with a suggestion that the addition of ADT improved biochemical PFS especially in patients with high-risk factors such as Gleason Score ≥8 and in the group with initially negative surgical margins. Conclusions: ADT combined with SRT appears to improve OS in patients with a PSA level before SRT of ≥0.7 ng/mL. In patients without persistent PSA after prostatectomy and PSA levels of <0.7 ng/mL, ADT should not routinely be used, but may be considered in patients with additional risk factors such as Gleason Score ≥8 and negative surgical margins.